Potensi Pengembangan Tanaman Pisang : Tinjauan Syarat Tumbuh dan Teknik Budidaya Pisang Dengan Metode Bit - Marthen P. Sirappa (AgroSainT, 2021)
Banana plant is one of the tropical fruit horticultural commodity that have high potential and economic value. The nutritional content and benefits of banana plants are quite a lot. Bananas are rich in vitamins and minerals and provide better energy than some other fruit crops. The benefits of bananas as a food function, health function, socio-cultural function and economic function. Harvested area and banana production in Indonesia tend to increase every year due to increased utilization. In addition to the fruit for food in the form of fresh fruit, semi-finished materials or in the form of other processed products, other plant parts which are waste such as stems, leaves and banana weevil can also be used for various other purposes. Generally, banana waste in Indonesia has not been utilized optimally even though in some countries it has high economic value, such as banana leaves and stems. Banana plants are easy to develop because they can grow in various places, in the tropics from the lowlands to the highlands. One easy and inexpensive method of propagation of bananas is the conventional method using banana weevil (bits) by turning off the growing point. The plants selected for the mother tree can be mature clumps that have already produced fruit and produce saplings, healthy clumps and free from pests and diseases. Propagation by weevil (bit method) can be done in two ways, namely : (1) the bulb is sown first and after growing the new shoots are split, and (2) the bulb is split first according to the eye of the shoot and then sown. Seedlings that have grown are placed in the shade until the age of 1 month and then adjustments are made in the open slowly until the age of 3-4 months, the seedlings are ready to be transferred to the field. Keywords: banana potential, fruit benefits, waste potential, weevil, bit method